(untitled) (International Journal of Medical and Surgical Sciences, 2016)
Periodontitis is a chronic local inflammatory disease of tissue supporting the teeth that leads to progressive loss of periodontal ligament and alveolar bone. Smoking is a known risk factor for many diseases and increasing evidence suggests that smoking negatively affects periodontal health. Cigarette smoking increased periodontal pathogenic bacterial flora, increasing their pathogenicity and alterations in the periodontal tissue, however the effect of smoking is not directly to these bacteria. Nicotine causes a decreased blood flow and decreased capillary hindering the immune response against pathogenic bacteria. In addition, the immune system is suppressed, so the action of leukocytes is poorly effective against periodontal disease. In conclusion, smoking, mainly nicotine, affects the gingival blood flow, cytokine production, the neutrophil function, replacement of connective tissue and because of these factors, increases the number of periodontal pathogenic bacteria which negatively affects the periodontal tissue.